Pengembangan E-Media Augmented Reality Berbasis Inquiry-Based Learning untuk Meningkatkan Minat Belajar Visualisasi Sejarah Manusia Purba - Mohamad Furqon; Ira Palupi Ayuningtyas; Fadilah Falah Syifa; Rizal Nurzuli; Pramesti Rahmadiyani (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2025)
This study aims to develop and evaluate the effectiveness of an Augmented Reality (AR)-based learning media using an Inquiry-Based Learning (IBL) model to enhance history learning interest among Grade X students at SMA NU Hasyim Asy’ari Tarub. The research was motivated by the low student interest caused by monotonous and traditional teaching methods. Employing a Research and Development (R&D) approach with the ADDIE model, the media was designed to feature interactive 3D objects of prehistoric humans, including Homo Soloensis, Pithecantropus erectus, and Homo Florensiensis, supplemented with audio and video. The application was developed using Unity 3D and Vuforia for Android devices. Validation from material, media, and language experts yielded scores of 49, 49, and 46 respectively, categorizing the media as "highly feasible." Classroom implementation garnered a very positive response with an average score of 116.4 from 26 students. A paired sample t-test comparing pre-test and post-test scores showed a statistically significant increase in learning interest, with a mean score difference of 14.40 at a 95% confidence level. These findings conclude that the AR-IBL learning media is highly effective and suitable for increasing student engagement and interest in history.